Design and Development of Solar Panel Current-Voltage Characterization Instrument Using Arduino Nano Board: Design and Development of Solar Panel Current-Voltage Characterization Instrument Using Arduino Nano Board - Chuenwattanapraniti, Chokchai; Rungsiyopas, Montana (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2023)
It is necessary to measure the generation performance of solar panels installed on site since the yield of electricity produced by solar panels depends on many environmental factors. Therefore, this paper presents the design and development of a simple, small, and low-cost instrument for measuring the electrical characteristics of solar panels. The proposed instrument is equipped with the Arduino microcontroller board responsible for controlling and signal processing in conjunction with the capacitor charging circuit that sweeps the panel output voltage. The instrument’s display on the Human Machine Interface (HMI) screen has 2 formats including a current-voltage graph and a table showing electrical parameters for the diagnosis purpose. The 4% of maximum discrepancy between the test results carried out from the proposed instrument and a commercial device under different solar irradiance and the partial shading conditions confirmed that the proposed instrument is comparable with the commercial one.